Effect of aging on acute pancreatitis through gut microbiota - Jing, Hui; Chang, Qimeng; Xu, Yayun; Wang, Jianfa; Wu, Xubo; Huang, Jiating; Wang, Lishun; Zhang, Ziping (Frontiers in Microbiology, 2022)
Background Compared to younger people, older people have a higher risk and poorer prognosis of acute pancreatitis, but the effect of gut microbiota on acute pancreatitis is still unknown. We aim to investigate the effect of aging gut microbiota on acute pancreatitis and explore the potential mechanism of this phenomenon. Methods Eighteen fecal samples from healthy adult participants, including nine older and nine younger adults were collected. C57BL/6 mice were treated with antibiotics for fecal microbiota transplantation from older and younger participants. Acute pancreatitis was induced by cerulein and lipopolysaccharide in these mice. The effect of the aged gut microbiota was further tested via antibiotic treatment before or after acute pancreatitis induction. Results The gut microbiota of older and younger adults differed greatly. Aged gut microbiota exacerbated acute pancreatitis during both the early and recovery stages. At the same time, the mRNA expression of multiple antimicrobial peptides in the pancreas and ileum declined in the older group. Antibiotic treatment before acute pancreatitis could remove the effect of aging gut microbiota, but antibiotic treatment after acute pancreatitis could not. Conclusion Aging can affect acute pancreatitis through gut microbiota which characterizes the deletion of multiple types of non-dominant species. This change in gut microbiota may potentially regulate antimicrobial peptides in the early and recovery stages. The level of antimicrobial peptides has negative correlations with a more severe phenotype.